2022-RA-1251-ESGO P-cadherin: a promising prognostic biomarker for homologous repair proficient high grade serous ovarian carcinoma. (20th October 2022) - Canario, Rita; Morgado, Inês; Ribeiro, Ana Sofia; Mendes, Nuno; Lopes, Paula; Teixeira, Manuel R; Bartosch, Carla; Paredes, Joana
Abstract : Introduction/Background: Homologous repair (HR) proficient tumours constitute 2/3 of high grade serous ovarian carcinoma (HGSOC), being associated with worse prognosis. Therefore, the identification of clinically relevant biomarkers is an urgent unmet clinical need. Once classic cadherins are transmembrane glycoproteins involved in cell-cell adhesion that are frequently deregulated in cancer, we aimed to: 1) characterize the expression pattern of E-cadherin ( CDH1), N-cadherin ( CDH2) and P-cadherin ( CDH3 ); 2) evaluate their prognostic impact in terms of overall survival (OS), according to HR status. Methodology: Retrospective study using a convenience sample of archive human tissue (Fallopian tube epithelium (FTE), serous precursor lesions and chemo-naïf HGSOC) from a Portuguese cancer centre. In vitro and in silico validation performed using HGSOC cell lines (BG1 and OVCAR4 cell lines) and CCLE database, respectively. Protein expression evaluated using immunohistochemistry (H-scoring system) and western blot. Comparisons between groups were made using T-test and X 2, where appropriate. Survival analyses were estimated using Kaplan-Meier analysis and Log-rank test. Results: We included 321 samples (130 FTE, 53 precursor lesions and 138 HGSOC; 41.2% BRCA1/2 or RAD51D mutated) from 221 patients. All HGSOC co-expressed the 3 cadherins (28% with high co-expression scores). Expression pattern did not differ according to HR status. P-cadherin was significantly upregulated both in precursor lesions and HGSOC, when compared with FTE. CDH3 expression was positively correlated with CDH1, EpCAM and GRHL2 and inversely correlated with VIM, both in silico and in vitro . HGSOC with high cadherin co-expression and high P-cadherin expression were significantly associated with shorter OS in the HR proficient subgroup. Conclusion: Our results suggest that P-cadherin upregulation may be an early event in the serous carcinogenesis and a poor prognosis biomarker in HR proficient HGSOC. Functional assays are currently ongoing to unravel the biological mechanisms underlying P-cadherin role in this subgroup.